Tanggung Jawab Pengurus Perseroan dalam Kepailitan Badan Hukum Perseroan Perorangan - Amirah Zalfa Arindya (Jurist-Diction, 2022)
AbstractThe existence of a new type of Limited Liability Company (PT) in the Job Creation Law, namely the Individual Company Legal Entity, aims to facilitate Micro and Small Business (UMK) actors. An individual company has a character limited liability like Capital Partnership of PT, the difference is that the establishment of an individual company founded by one person, who is the only party filling the position of the company's organs. However, the two entities have significant differences, mainly in the position of the Company's organs and management, so that they can have different legal consequences in various aspects including bankruptcy. With the legal research method, reviewing the laws and regulations with the aim of knowing the characteristics of an Individual company in Indonesia, and the form of responsibility of the company management in the bankruptcy of an individual company. From the results of the research, it is necessary to improve regulations, especially regarding the bankruptcy of individual companies which are UMK in accordance with the Job Creation Law and PP No. 8 of 2021, to protect that the formation of UMK Individual Companies as job creation and ease of doing business does not become a disaster for entrepreneurs whose Individual Companies are declared bankrupt. Keywords: Individual Company Legal Entity; Liability; Bankruptcy. AbstrakEksistensi Perseroan Terbatas (PT) baru dalam UU Cipta Kerja yaitu Badan Hukum Perseroan Perorangan bertujuan memudahkan pelaku usaha Mikro Kecil (UMK). Perseroan Perorangan berkarakter limited liability selayaknya PT Persekutuan Modal, perbedaannya pendirian Perseroan Perorangan didirikan oleh satu orang, yang menjadi satu-satunya pihak pengisi kedudukan organ Perseroan. Namun, kedua entitas tersebut memiliki perbedaan signifikan utamanya pada kedudukan organ Perseroan dan kepengurusannya sehingga dapat menimbulkan akibat hukum berbeda pada berbagai aspek termasuk kepailitan. Dengan metode penelitian hukum, menelaah peraturan perundang-undangan dengan tujuan untuk mengetahui karakteristik Perseroan Perorangan, dan bentuk Tanggung Jawab Pengurus Perseroan dalam Kepailitan Perseroan Perorangan. Dari hasil penelitian, penyempurnaan regulasi dibutuhkan khususnya terkait kepailitan Perseroan Perorangan yang merupakan UMK sesuai UU Cipta Kerja dan PP No. 8 Tahun 2021, untuk melindungi agar pembentukan Perseroan Perorangan UMK sebagai penciptaan lapangan kerja dan kemudahan berusaha tidak menjadi malapetaka bagi pengusaha yang Perseroan Perorangannya dinyatakan pailit.Kata Kunci: Badan Hukum Perseroan Perorangan; Tanggung Jawab; Kepailitan.